Statewide Dissemination of an Evidenced-Based Email Walking Program Delivered Through Cooperative Extension - Richards, Elizabeth A.; Woodcox, Stephanie; Forster, Anna (Frontiers in Public Health, 2020)
Using the RE-AIM framework, this study evaluates the statewide dissemination of an evidenced-based, email-delivered physical activity intervention implemented through Cooperative Extension. The Get WalkIN’ program is comprised of 16 email messages sent over 12 weeks. Email messages target social cognitive theory constructs of self-efficacy, goal-setting, self-monitoring, and social support. Program reach, effectiveness, adoption, implementation, and maintenance were assessed with quantitative measures in a pre-post design. Findings indicate that within the Extension system, program adoption was high and program maintenance was moderate. Program effectiveness was demonstrated with an increase of 77.1±49.9 minutes in weekly walking post-program. This increase in walking was maintained three months post-program. Capturing data on the implementation process was challenging. Overall, the results indicate success in program adoption and maintenance with further efforts needed to improve follow-up data collection from participants.